Closed system behaviour of argon in osumilite records protracted high‐T metamorphism within the Rogaland–Vest Agder Sector, Norway. (11th April 2019) - Blereau, Eleanore; Clark, Chris; Jourdan, Fred; Johnson, Tim E.; Taylor, Richard J. M.; Kinny, Peter D.; Danišík, Martin; Hand, Martin; Eroglu, Ela
Abstract: Here, we present results of the first 40 Ar/ 39 Ar dating of osumilite, a high‐ T mineral that occurs in some volcanic and high‐grade metamorphic rocks. The metamorphic osumilite studied here is from a metapelitic rock within the Rogaland–Vest Agder Sector, Norway, an area that experienced regional granulite facies metamorphism and subsequent contact metamorphism between 1, 100 Ma and 850 Ma. The large grain size (~1 cm) of osumilite in the studied rock, which preserves a nominally anhydrous assemblage, increases the potential for large portions of individual grains to have remained essentially unaffected by the effects of diffusive argon loss, potentially preserving prograde ages. Step‐heating diffusion experiments yielded a maximum activation energy of ~461 kJ/mol and a pre‐exponential factor of ~8.34 × 10 8  cm 2 /s for Ar diffusion in osumilite. These parameters correspond to a relatively high closure temperature of ~620°C for a cooling rate of 10°C/Ma in an osumilite crystal with a 175 µm radius. Fragments of osumilite separated from the sample preserve a range of ages between c . 1, 070 and 860 Ma. The oldest ages are inferred to date the growth of coarse‐grained osumilite during prograde granulite facies regional metamorphism, which pre‐date contact metamorphism that has historically been ascribed to the growth of osumilite in the region. The majority of fragments record ages between c . 920 and 860 Ma, inferred to reflect the growth of osumilite and/or diffusive argon loss during contact metamorphism. The retention of old 40 Ar/ 39 Ar dates was facilitated by the low diffusivity of Ar in osumilite (i.e. a closed system), large grain sizes, and anhydrous metamorphic conditions. The ability to date osumilite with the 40 Ar/ 39 Ar method provides a valuable new thermochronometer that may constrain the timing and duration of high‐ T magmatic and metamorphic events.